Cardiology Consult Manual (Springer International Publishing, 2018)
This book comprehensively covers the latest advances in cardiovascular medicine. Key diagnostic and treatment points are reviewed across a range of cardiovascular issues, including concurrent cardiac problems, patients with cancer, peri-operative surgical and post-trauma patients, patients in the emergency department, pregnancy in the obstetric units, and the care of critically ill patients in medical and surgical intensive care units. Cardiology Consult Manual provides a detailed and clinically relevant guide for the cardiology practitioner of the potential cardiac issues encountered within the cardiology consult service and also a range of professionals in related disciplines. It therefore provides an important resource for all cardiology trainees, fellows, practitioners and health care providers involved in the management of patients with cardiovascular disease. .